Perceptions of the Fourth Agricultural Revolution: What's In, What's Out, and What Consequences are Anticipated?. Issue 2 (25th September 2020) - Barrett, Hannah; Rose, David Christian
Abstract: Technological advancement is seen as one way of sustainably intensifying agriculture. Scholars argue that innovation needs to be responsible, but it is difficult to anticipate the consequences of the 'fourth agricultural revolution' without a clear sense of which technologies are included and excluded. The major aims of this article were to investigate which technologies are being associated with the fourth agricultural revolution, as well as to understand how this revolution is being perceived, whether positive or negative consequences are given equal attention, and what type of impacts are anticipated. To this end, we undertook a content analysis of UK media and policy documents alongside interviews of farmers and advisers. We found that the fourth agricultural revolution is associated with emergent, game‐changing technologies, at least in media and policy documents. In these sources, the benefits to productivity and the environment were prioritised with less attention to social consequences, but impacts were overwhelmingly presented positively. Farmers and advisers experienced many benefits of technologies and some predicted higher‐tech futures. It was clear, however, that technologies create a number of negative consequences. We reflect on these findings and provide advice to policy‐makers about how to interrogate the benefits, opportunities, and risks afforded by agricultural technologies.